Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1100/2012/263572
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial, Anti-Inflammatory, Antiparasitic, and Cytotoxic Activities ofLaennecia confusa

Abstract: The current paper investigated the potential benefit of the traditional Mexican medicinal plant Laennecia confusa (Cronquist) G. L. Nesom (Asteraceae). Fractions from the hexane, chloroform, methanol, and aqueous extracts were analyzed for antibacterial, antifungal, anti-inflammatory, and antiparasitic activities. The antimicrobial activity of the extracts and fractions was assessed on bacterial and fungal strains, in addition to the protozoa Leishmania donovani, using a microdilution assay. The propensity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Plates were placed in a humidified atmosphere at 37°C supplemented with 5% CO 2 for 24 h. Untreated THP-1 cells and DMSO were used as negative controls, whereas 5% hydrogen peroxide was used as a positive control. Propidium iodide (PI) was used to evaluate membrane damage [18]. The half maximal inhibitory concentration (IC 50 ) was calculated by plotting the compound concentrations against the percentage of damaged cells.…”
Section: Methodsmentioning
confidence: 99%
“…Plates were placed in a humidified atmosphere at 37°C supplemented with 5% CO 2 for 24 h. Untreated THP-1 cells and DMSO were used as negative controls, whereas 5% hydrogen peroxide was used as a positive control. Propidium iodide (PI) was used to evaluate membrane damage [18]. The half maximal inhibitory concentration (IC 50 ) was calculated by plotting the compound concentrations against the percentage of damaged cells.…”
Section: Methodsmentioning
confidence: 99%
“…Antibacterial, antifungal and antiparasitic activities of extracts of Mexican medicinal plant Laennecia confusa of Asteraceae family were confirmed. Extracts including cyanogenic and cardiotonic glycosides demonstrated antibacterial activity against Staphylococcus aureus and antiparasitic activity against Leishmania donovani and were also found to be cytotoxic to macrophages(Martinez Ruiz et al, 2012).…”
mentioning
confidence: 99%
“…The genus Conyza(Asteraceae) is comprised of approximately 400 species and several species are known for their use in traditional medicine. 39 Many ethnobotanical studies have documented the use of C. bonariensis in the ethnomedicines of different cultures. [40][41][42][43][44] Previous studies have confirmed bioactive properties for specific Conyza species.…”
Section: Discussionmentioning
confidence: 99%